(untitled) (Research, Society and Development, 2020)
The increase in the weight and traffic of agricultural machinery associated with the reduction in the time of execution of activities, has resulted in greater soil compaction. Thus, the objectives of the research were to evaluate the physical and dynamic parameters of the soil and the operational performance in function of different levels of traffic of agricultural tractor under different conditions of track surfaces. The experiment was carried out in an area of ​​the State University of Maringá - UEM, Umuarama Regional Campus. The experimental design was a factorial arrangement in randomized blocks, the factors being four (4) track surface conditions (grated soil, low mowing, medium mowing and without mowing), with five traffic levels (1; 2; 3; 4 and 5 strides of the tractor on the same track) and 3 repetitions. The effect of traffic in relation to settlement on the ground that showed the greatest difference between treatments was in the first pass of the tractor on the same trail. The straw on the surface reduced the resistance to penetration, density and settlement, but increased the soil moisture.